2018
DOI: 10.1097/pq9.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Unexpected Returns to Orthopedic Hand Clinic: Improving Efficiency of Health Care Delivery

Abstract: Purpose:An unexpected return to clinic (URTC) visit can place a substantial financial burden on patients and families while stressing the health care system. Our SMART aim was to decrease the rate of URTC visits from 1.8 per 100 patient follow-up visits by 50% using quality improvement methodology.Methods:The rate of URTC visits was tracked at our tertiary care pediatric hospital from February 1, 2014, to May 31, 2015, using a weekly P-chart. Interventions were studied from January 1 to May 31, 2015. Pareto ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…24 A study in 2018 found that the average patient cost of an unexpected visit to return to hand clinic was $350 of medical charges and $70 of nonmedical, out-of-pocket costs for lost work and travel. 25 This study is not without limitations. Given its retrospective nature, it was difficult to capture all symptoms patients were experiencing during follow-up visits.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…24 A study in 2018 found that the average patient cost of an unexpected visit to return to hand clinic was $350 of medical charges and $70 of nonmedical, out-of-pocket costs for lost work and travel. 25 This study is not without limitations. Given its retrospective nature, it was difficult to capture all symptoms patients were experiencing during follow-up visits.…”
Section: Discussionmentioning
confidence: 89%
“… 24 A study in 2018 found that the average patient cost of an unexpected visit to return to hand clinic was $350 of medical charges and $70 of nonmedical, out-of-pocket costs for lost work and travel. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have examined the role of cast care education in the incidence of cast complications. Little et al (2018) and Newman and Gaffney (2018) both examined the effect of standardized cast care education on the rate of unplanned RTC. Both studies noted a decrease in unplanned RTC with the combination of verbal and written cast care instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized patient and family education, adequate telephone triage, and appropriate follow-up can prevent such visits and decrease unnecessary expenses both on the patient and institutional ends (DiPaola et al, 2014; Doan et al, 2019; Jackson et al, 2018; Rogers & Attia, 2017; Sawyer et al, 2010). There is sufficient evidence to support an innovation that addresses varying learning styles; several studies demonstrate success with multimodal approaches, which include verbal, written, and video instructions (Ismail et al, 2016; Little et al, 2018; Newman & Gaffney, 2018).…”
mentioning
confidence: 99%